2015
DOI: 10.1186/s13058-015-0579-y
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of epithelial-mesenchymal transition phenotype in the tamoxifen-resistant breast cancer cell: a new role for G protein-coupled estrogen receptor in mediating tamoxifen resistance through cancer-associated fibroblast-derived fibronectin and β1-integrin signaling pathway in tumor cells

Abstract: IntroductionAcquired tamoxifen resistance remains the major obstacle to breast cancer endocrine therapy. β1-integrin was identified as one of the target genes of G protein-coupled estrogen receptor (GPER), a novel estrogen receptor recognized as an initiator of tamoxifen resistance. Here, we investigated the role of β1-integrin in GPER-mediated tamoxifen resistance in breast cancer.MethodsThe expression of β1-integrin and biomarkers of epithelial-mesenchymal transition were evaluated immunohistochemically in 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
79
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(91 citation statements)
references
References 48 publications
(82 reference statements)
10
79
1
1
Order By: Relevance
“…Despite major advances in breast cancer treatment and management, and successful treatment of ER-positive breast cancer with tamoxifen and aromatase inhibitors, one third of women with estrogen receptorα (ER)-positive breast cancer suffer from recurrent disease within fifteen years (33). As EMT has been observed in tamoxifen (TAM)-resistant MCF-7 breast cancer cells (30,34,35) and given the association between HOXB7 and EMT in breast cancer (11), HOXB7 protein might possibly play a role in tamoxifen resistance and ensuing tumor progression. Evidence supporting this hypothesis was elucidated by Jin and collaborators through work that demonstrated that HOXB7 overexpression conferred TAM-resistance to ER+ breast cancer cells through the HOXB7-dependent transcriptional induction of EGFR (3,11).…”
Section: Discussionmentioning
confidence: 99%
“…Despite major advances in breast cancer treatment and management, and successful treatment of ER-positive breast cancer with tamoxifen and aromatase inhibitors, one third of women with estrogen receptorα (ER)-positive breast cancer suffer from recurrent disease within fifteen years (33). As EMT has been observed in tamoxifen (TAM)-resistant MCF-7 breast cancer cells (30,34,35) and given the association between HOXB7 and EMT in breast cancer (11), HOXB7 protein might possibly play a role in tamoxifen resistance and ensuing tumor progression. Evidence supporting this hypothesis was elucidated by Jin and collaborators through work that demonstrated that HOXB7 overexpression conferred TAM-resistance to ER+ breast cancer cells through the HOXB7-dependent transcriptional induction of EGFR (3,11).…”
Section: Discussionmentioning
confidence: 99%
“…In tamoxifen-resistant breast tumors, G protein-coupled estrogen receptor (GPER)/epidermal growth factor receptor (EGFR)/ extracellular regulated protein kinase (ERK) signaling enhances β1-integrin expression and activates downstream kinases, contributing to CAF-induced cell migration [17]. Moreover, downstream kinases of β1-integrin including focal adhesion kinase, Src and AKT are activated in resistant cells, potentially involved in the interaction between cancer cells and CAFs [17], highlighting the persistent tumor-stroma communication in a biologically dynamic TME.…”
Section: Cancer-associated Fibroblastsmentioning
confidence: 99%
“…Moreover, downstream kinases of β1-integrin including focal adhesion kinase, Src and AKT are activated in resistant cells, potentially involved in the interaction between cancer cells and CAFs [17], highlighting the persistent tumor-stroma communication in a biologically dynamic TME. More importantly, CAFs establish a synergistic relationship with cancer cells, contributing to their malignancy and therapeutic resistance.…”
Section: Cancer-associated Fibroblastsmentioning
confidence: 99%
“…The development of endocrine therapy resistance in primary breast cancer is associated with poor prognosis and, in cell line models and clinical samples of endocrine resistance, a transition to more aggressive tumor phenotypes that have undergone partial EMT (14)(15)(16)(17). The cancer therapeutic TRAIL has been shown to preferentially induce cell death in breast cancer cell lines that exhibit a more mesenchymal phenotype (35).…”
Section: Acquired Endocrine-resistant Breast Cancer Cell Lines Develomentioning
confidence: 99%
“…Thus, the majority of patients with advanced disease and up to 30% of ERþve patients in the adjuvant setting will acquire resistance to the inhibitory effects of their endocrine treatment (12,13). The acquisition of resistance manifests with a partial epithelial-mesenchymal transition (EMT) and increased migratory and invasive activity both in anti-estrogen-resistant cell line models (14) and in clinical samples (14)(15)(16)(17). Furthermore, a subset of tumor-initiating cells with stem-like characteristics (cancer stem cells: CSCs) is enriched in tamoxifen-resistant breast cancers and may demonstrate resistance to endocrine therapies, thus contributing to disease recurrence and metastatic progression (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%